Three new species of the genus Barsine Walker (Lepidoptera: Erebidae: Arctiinae) from Taiwan - Volynkin, Anton V. (Zootaxa, 2021)
Three new species of the genus Barsine Walker, 1854 are described from the island of Taiwan: B. geometroides sp. n., B. wui sp. n. and B. witti sp. n. The diagnostic comparison is made with B. ponlai Wu, Fu & Chang, 2013, B. mactans Butler, 1877 and B. callorufa Wu, Fu & Chang, 2013. Adults together with the male and the female genitalia of the new and the similar species are illustrated.